Effect of resistance training on the biomechanics and accuracy of serve receiving skills in volleyball - Taha Idrees , Muna; Muhsun Yasir , Alaa; Mohammed Rashied , Jasim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study aimed to identify the effect of resistance training on the biomechanics and accuracy of serve receiving skills in volleyball. The research community was composed of 26 young volleyball players of Baghdad volleyball clubs. A total of 4 players were selected for the preliminary experiment, while 14 participants were recruited as the main sample for the study. In the present study, a set of resistance exercises were designed by the researchers for the volleyball players of the sample. Exercises were performed by the sample participants during the course of study. The biomechanical variables considered in the present study were: Preparation moment (shoulder joint angle, hip angle, knee joint angle), moment of propulsion (shoulder joint angle, hip angle, knee joint angle). Based on the findings of the present study, the researchers concluded that the resistance exercises had a positive impact on the biomechanics and accuracy of serve receiving skills in the participants.